PERSEPSI SISWA TERHADAP KEGIATAN PERSEPSI SISWA TERHADAP PENGEMBANGAN DIRI SENI TARI DI SMP N 2 PADANG PANJANG - Gustia Ningsih; Zora Iriani; Yuliasma Yuliasma (SENDRATASIK UNP, 2017)
AbstrackThe purpose of Students at SMP N 2 Padang Panjang unwillingly attended self-development activities of dancing class. Students were less serious in attending self-development of dancing class during learning. The purpose of this study was to describe students' perceptions on self-development activities of dancing class at SMP N 2 Padang Panjang.This research type was qualitative research which used descriptive approach. The population of this research was the students of grade VII at SMP N 2 Padang Panjang who joined self-development activities of dancing class. The research used primary data. In collecting the data in the field, observation sheets, interviews and cameras were used as the instruments of the research.The findings of this research showed that students 'perceptions on self-development activities of dancing class in SMP N 2 Padang Panjang were, the students' intentions and talents to join the activities, but they did not agree with the teacher’s way and material selection. As a result, the students thought that the activity was boring. The indicators of students' perceptions at SMP N 2 Padang Panjang were 1) the acceptance of students in which the students were interested and talented but they could not focus due to the hasty way of teachers so that students could not understand the material well and they could not express their talent well, 2) Students’ understanding in which the students were not familiar with dance material given by using video; the students did not want to do it, 3) students’ assessment in which students like their teachers but the hasty and repeated way the teachers used in delivering the materials made students feel bored.   Keywords: Student's Perception on Self Development Activities of DancingAbstrack The purpose of Students at SMP N 2 Padang Panjang unwillingly attended self-development activities of dancing class. Students were less serious in attending self-development of dancing class during learning. The purpose of this study was to describe students' perceptions on self-development activities of dancing class at SMP N 2 Padang Panjang.This research type was qualitative research which used descriptive approach. The population of this research was the students of grade VII at SMP N 2 Padang Panjang who joined self-development activities of dancing class. The research used primary data. In collecting the data in the field, observation sheets, interviews and cameras were used as the instruments of the research.The findings of this research showed that students 'perceptions on self-development activities of dancing class in SMP N 2 Padang Panjang were, the students' intentions and talents to join the activities, but they did not agree with the teacher’s way and material selection. As a result, the students thought that the activity was boring. The indicators of students' perceptions at SMP N 2 Padang Panjang were 1) the acceptance of students in which the students were interested and talented but they could not focus due to the hasty way of teachers so that students could not understand the material well and they could not express their talent well, 2) Students’ understanding in which the students were not familiar with dance material given by using video; the students did not want to do it, 3) students’ assessment in which students like their teachers but the hasty and repeated way the teachers used in delivering the materials made students feel bored. 62 Keywords: Student's Perception on Self Development Activities of Dancing Class at SMP N 2 Padang Panjang